COVID-19-related knowledge, attitudes and practices: a mixed-mode cross-sectional survey in Liberia - Wilson, Josiah Brown; Deckert, Andreas; Shah-Rohlfs, Rupal; Kyei, Nicholas N. A.; Dahn, Lauretta Copeland; Doe-Rogers, Rosalita; Hinneh, Augustine Bowuo; Johnson, Lydia Wortee; Natt, Gudgy Dweh; Verdier, Joseph Augustus; Vosper, Adele; Louis, Valérie R.; et al. (BMJ open, 2021)
Objectives To examine the knowledge, attitudes and practices (KAP) of COVID-19 of rural and urban residents in Liberia to inform the development of local social and behaviour change communication strategies. - Design Cross-sectional, mixed-mode (online and telephone) survey using non-probability sampling. - Setting All 15 counties in Liberia with a focus on Maryland County. - Participants From 28 May to 28 June 2020, data were collected from a total of 431 adults aged 18 years and older (telephone 288 (66.8%); online 143 (33.2%)) out of a total of 741 contacts. - Main outcome measures KAP scores. Frequencies and proportions were calculated, followed by univariate and multivariable analyses to examine the association between KAP scores and the sociodemographic variables. - Results Around 69% of the online survey respondents were younger than 35 years of age, compared with 56% in the telephone interviews. The majority (87%) of online respondents had completed tertiary education, compared with 77% of the telephone respondents. Male participants, on average, achieved higher knowledge (52%) and attitude scores (72%), in contrast to females (49% and 67%, respectively). Radio (71%) was the most cited source for COVID-19 information, followed by social media (63%). After controlling for sociodemographic variables, adaptive regression modelling revealed that survey mode achieved 100% importance for predicting knowledge and practice levels with regard to COVID-19. - Conclusions The survey population demonstrated moderate COVID-19 knowledge, with significant differences between survey mode and educational level. Correct knowledge of COVID-19 was associated with appropriate practices in Maryland County. Generalisation of survey findings must be drawn carefully owing to the limitations of the sampling methods. Yet, given the differences in knowledge gaps between survey modes, sex, education, occupation and place of residence, it is recommended that information is tailored to different audiences.
Online issue publication July 27, 2021
Gesehen am 13.08.2021